Understanding Sexuality in the Later Years - Smita Bammidi (Indian Journal of Gerontology, 2009)
A significant gap exists between the reality and meaning of sexuality – sensuality for the elderly and the persistent, widespread mythology and destructive stereotypes associated with this age group. Evidence indicates the importance and centrality of sexuality through out the development of the human family from primitive to modern times. Research, although still rudimentary, has provided data which indicated the continuity of the interest in and need and capacity for sexual expression among human beings into the ninth decade of their lives. Most of the early research on sex focused on the physical acts of intercourse and orgasm but ignored the whole person. It has now become increasingly evident that the whole person -personality, physiology, and integrated life experiences – is involved in sexual-sensual behavior. There is little doubt that gender identity, role ascription, and the qualities of femaleness and maleness contribute to the sexual behavior of every human being; yet these attributes are largely submerged in the neuterdom assumed to be the state of the late middle and older ages. The many jokes and stories that ridicule sexuality in the later years accurately reflect our society’s hostile, insulting attitudes towards both sex and old age. The stereotyping of older men and women as sexless is the ultimate example of ageism. But, as with other forms of prejudice, this devastating myth about the nature of ageing can be laid to rest once we obtain and disseminate correct information regarding various myths about sexuality in the elderly from physiological, psychological and social perspectives.